A warm environment reduces exogenous glucose oxidation and endurance performance during cycling with facing airflow - Reynolds, K; Funnell, M; Collins, A; Mears, S; Pugh, J; James, L. (Medicine & Science in Sports & Exercise, 2025)
Exercise in warm environments increases thermal/cardiovascular strain and decreases gastrointestinal (GI) integrity and endurance performance. However, laboratory-based studies have provided little to no facing airflow, potentially exacerbating these effects, particularly for cycling, where convective cooling may be a major contributor to thermal balance.